Working towards Inclusive Growth Skill Development Mission - Singh, Shashi; Singh, Ajay; Singh, Kiran (JOURNAL OF INDIAN EDUCATION, 2012)
Skills and knowledge are the driving forces of economic growth and social development of any country. India’s position on the skill and research orientation of individuals and institutions are precariously at low level as compared to major economies of the world. Fast growth rate and poor skill index of its population has been the major challenge and obstacle of India to fulfill its cherished dream of inclusive and sustainable growth. Government of India is consistently working and making efforts through its plan policies and other major programmes to achieve these objectives. This paper tries to examine and evaluate the existing scenario of Indian education system and workforce skill index as compared to other major economies of the world. This paper will also study thoroughly the Skill Development Mission and its various dimensions and plans which will help in the generation of skillful population.